THE ESSENCE OF QUESTIONING AND EXPLICIT READING INSTRUCTION STRATEGY - Sa’dulloh Muzammil (AT-TURATS, 2014)
Teacher’s questioning may function to assist students comprehend more reading materials and to enable them to be proficient readers. Yet, the students may be less benefited from which if the teacher neither provides sufficient explicit reading strategy nor involves higher-level questions. Consequently, the teacher should pay more careful attentions as follows: 1) teacher should involve both lower- and high-lever questions; 2) teacher should provide students with explicit reading strategy; 3) teacher should be aware of the activities in reading phases: pre-, during-, and post-reading.